Államterek és Köztes-Európa - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2015)
Nowadays beside the expression of Central Europe often appears the technical term of Median Europe in the politico-geographical literature. Median Europe as a special geopolitical buffer zone between the Russian Empire and Europe had a very important historic role in the 19th and 20th centuries. The formation of Median Europe as a historical and geographical region shows close coherence with the evolution of territories of states of Eastern and Central Europe and of the Balkans. This region was one of the danger zones of our continent in the 19th and 20th centuries due to conflicting territorial processes. The fragmentation of the territories of states in the Balkans and the formation of huge territories of states in Eastern and Central Europe were parallel in the second half of the 19th century. These territorial fragmentations and formations also showed the expansion and alternation of the great powers of the region. They are the geographical evidences of the transfer of power in Europe. The existence, the territorial fragmentation and the politico-geographical function of Median Europe are parallel with the historical processes of Europe. The historic-geographical research on Median Europe could be the scientific framework of researches on the history of the Habsburg Monarchy and its successor states. Because of its special geopolitical function and position in the continent, Median Europe had several politico-geographical impulses through its history. These influences and the formation of states along the border of the region determined the development of the territories of states and powers in the different historical periods of Median Europe. The territorial changes of the Habsburg Monarchy and Poland (as typical states in Median Europe) are the most significant examples of this process. This essay gives an overall picture of the history of the territories of states in the Median Europe and presents the historical and politico-geographical contours of the region.